Penerapan Model Bivariat Menggunakan Copula Frank pada Jumlah Gol Hasil Pertandingan Liga 1 Indonesia 2019 - Naufal Fajar; Aceng Komarudin Mutaqin (Bandung Conference Series: Statistics, 2023)
Abstract. Indonesia is one of the countries that always organizes soccer competitions. Liga 1 is an Indonesian football league that brings together 18 of the best soccer teams from Indonesia. Each team played 34 times on a home-away system. The purpose of this thesis is to improve the quality of Indonesian football and mark the gradual league system of Indonesian football at a competitive level. Many studies have been conducted by researchers in various countries to process data on the number of goals scored in soccer matches for home and away teams from a soccer league. Joel Liden (2016) discusses the Copula Frank distribution followed by the marginal distribution, namely the Poisson distribution and the negative Binomial distribution, a distribution for data from discrete random variables. This thesis will discuss the application of the Copula Frank distribution to data on the number of goals for home and away teams from the highest caste Indonesian football league matches for 2018-2019 and to find out whether the Copula Frank distribution is a suitable opportunity distribution for modeling the case of the number of goals data. the. The distribution fit test used is the Chi-square test. As research material, secondary data from recording results obtained from PSSI.com will be used and presented as data on the results of the 2018-2019 Indonesian League 1 football match. The maximum likelihood estimator method is used to estimate the parameters of the discrete distribution. While the distribution fit test to be used is the chi-square test. As an application material, secondary data will be used as a result of recording obtained from rsssf.com and flashscore.com. The data that will be used contains information on the number of goals for the home team and the number of goals for the away team in the 2018-2019 Indonesian League 1 matches. The results of the application show that the bivariate Poisson distribution using Copula Frank is not suitable for modeling bivariate data on the number of goals for the home and away team in the Indonesian League 1 in 2018-2019. Abstrak. Indonesia merupakan salah satu negara yang selalu menyelenggarakan kompetisi sepak bola. Liga 1 merupakan liga sepak bola Indonesia yang mempertemukan 18 tim sepak bola terbaik dari Indonesia. Masing-masing tim bertanding sebanyak 34 kali dengan sistem kandang-tandang. Tujuan dibuat skripsi ini untuk meningkatkan kualitas sepak bola Indonesia dan menandai sistem liga bertahap sepak bola Indonesia di tingkat kompetitif. Sudah banyak penelitian yang dilakukan oleh para peneliti di berbagai negara untuk mengolah data jumlah gol hasil pertandingan sepak bola untuk tim kandang dan tim tandang dari suatu liga sepak bola. Joel Liden (2016) membahas distribusi Copula Frank diikuti oleh distribusi marjinal yaitu distribusi Poisson dan distribusi Binomial negatif, suatu distribusi untuk data dari peubah acak diskrit. Dalam Skripsi ini akan dibahas mengenai penerapan distribusi Copula Frank pada data jumlah gol tim kandang dan tim tandang hasil pertandingan Liga sepak bola Indonesia kasta tertinggi untuk tahun 2018-2019 dan untuk mengetahui apakah distribusi Copula Frank merupakan distribusi peluang yang cocok untuk memodelkan kasus data jumlah gol tersebut. Uji kecocokan distribusi yang digunakan adalah uji Chi-kuadrat. Sebagai bahan penelitian akan digunakan data sekunder hasil pencatatan yang diperoleh dari PSSI.com dan disajikan menjadi data hasil pertandingan sepakbola Liga 1 Indonesia tahun 2018-2019. Metode penaksir kemungkinan maksimum digunakan untuk menaksir parameter distribusi diskrit tersebut. Sedangkan uji kecocokan distribusi yang akan digunakan adalah uji chi-kuadrat. Sebagai bahan aplikasi akan digunakan data sekunder hasil pencatatan yang diperoleh dari yaitu rsssf.com dan flashscore.com. Data yang akan digunakan tersebut berisi informasi jumlah gol tim kandang dan jumlah gol tim tandang pertandingan Liga 1 Indonesia tahun 2018-2019. Hasil penerapan menunjukkan bahwa distribusi Poisson bivariat menggunakan Copula Frank tidak cocok untuk memodelkan data bivariat jumlah gol tim kandang dan tim tandang Liga 1 Indonesia tahun 2018-2019.